No synergistic effect of fecal microbiota transplantation and shugan decoction in water avoidance stress-induced IBS-D rat model - Meng, Yangyang; Feng, Ya; Hang, Lu; Zhou, Yan; Wang, Enkang; Yuan, Jianye (Frontiers in Microbiology, 2022)
Background It has been reported that 5-hydroxytryptamine (5-HT, serotonin) metabolism is involved in the pathogenesis of irritable bowel syndrome (IBS) and that either Shugan decoction (SGD) or fecal microbiota transplantation (FMT) can alleviate the symptoms of IBS in patients and animal models. But the synergistic effect of FMT and SGD on 5-HT metabolism and IBS symptoms has not been investigated. Aim The main purpose of this study is to observe the synergistic effect of FMT with SGD on symptoms and 5-HT metabolism in IBS-D rats induced by water avoidance stress (WAS). Moreover, the possible material basis of the FMT was investigated. Methods In experiment I, rats were randomly divided into seven groups. Control group: routine feeding; WAS→ Control group: routine feeding with fecal microbiota liquid (FML) 1 (derived from rats in WAS group) gavage since the fourth day; WAS group: 10 days WAS with routine feeding; SGD group: 10 days WAS with SGD gavage since the fourth day on the base of routine feeding; Control→ WAS group: 10 days WAS with FML2 (derived from rats in Control group) gavage since the fourth day with routine feeding; SGD→ WAS group: 10 days WAS with FML3 (derived from rats in SGD group) gavage since the fourth day with routine feeding; SGD + (Control→ WAS) group: 10 days WAS with SGD and FML2 (derived from rats in Control group) gavage since the fourth day with routine feeding. In experiment II, rats were randomly divided into three groups. Control group: routine feeding; Control→ WAS group: 10 days WAS with FML2 gavage since the fourth day with routine feeding; FControl→ WAS group: 10 days WAS with FML2 filtrate gavage since the fourth day. The number of fecal pellets output (FPT) and the pain pressure threshold (PPT) were recorded. The histological changes in colon mucosa were observed by hematoxylin-eosin (HE) stain. The number of enterochromaffin cells (ECs), the content of 5-HT, and the expression of serotonin reuptake transporter (SERT) protein in the colon were measured by immunofluorescence or western blotting. Results Compared with that in the control group, the PPT and the expression of SERT in the WAS group and that in the WAS→ Control group were decreased with the increased number of ECs and the level of 5-HT in colon. But the FPT was not increased in the WAS→ Control group although that was increased in the WAS group. Compared with that in the WAS group, the FPT, the PPT, the number of ECs, the level of 5-HT, and the expression of SERT protein in colon in the SGD group, control→ WAS group, SGD→ WAS group, and SGD+(Control→ WAS) group were all recovered. The recovery of these indicators in the Control→ WAS group and that in the FControl→ WAS group was not significantly different. Conclusion No synergistic effect of SGD with FMT on IBS symptoms induced by WAS was found. The metabolites of intestinal microbiota may be the main active substances of the FML derived from normal rats to alleviate WAS-induced IBS symptoms.